Helmintos de la República de Costa Rica XII. Zonorchis costarncensis n. sp. (Trematoda, Dicrocoeliidae) parásito de vías biliares de Gymnostinops montezuma (lcteridae) - Brenes, Rodrigo Ramón; Jiménez-Quirós, Otto (Revista de Biología Tropical, 1959)
1. The presence of the genus Zonorchis Travassos, 1944, is reported for the first time for the Middle American area North of Panama. 2. Zonorchis costarricensis n. sp. is described, a parasite in biliary ducts of Gymnostinops montezuma, this being the first record of Zonorchis parasitism in a member of the Icteridae.